Geodesic Convexity of graphs: partition and geodetic sets - Artigas, Danilo; Dantas, Simone; Dourado, Mitre (Cadernos do IME - Série Informática, 2022)
This work describes the contribution of Artigas, Dantas, Dourado, and Szwarcfiter on the topic of convexity in the context of geodesic convex partitions, covers and geodetic sets from 2008 to 2013.